(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is the best way to deal with it as it cures the root cause of any problem. According to Ayurveda skin diseases are caused by imbalance of Doshas and therefore treatment depends on imparting harmony and balance for the individual. In Ayurveda skin diseases are included under the heading of Kushta and Kshudrarogas. Vyanga is one among the Kshudra rogas, even though Vyanga is a Kshudraroga it produces a great misery for the person due to dark discoloration of the skin, mostly over the face, occasionally on neck and rarely in forearms. Vyanga is a pathological situation of the facial skin which is produced due to the vitiation of Vata, Pitta, Rakta and Manasika Nidanas such as Krodha (anger), Shoka (sorrow), and Ayasa (mental exertion) are main culprits, these producing cardinal features such as Niruja (painless), Tanu (thin) and Shyavavarna Mandalas (bluish black colour patches). The Lakshanas of Vyanga are explained by different authors in the classical texts of Ayurveda under the heading of Kshudra rogas, Sushruta samhita, Ashtanga samghraha, Madhava nidana, Ashtanga hrudaya, Bhava prakasha, Sharangadhara samhita. In the context of Vyanga both Shodhana and Shamana chikitsa are explained in the form of Raktamokshana, Lepa, Abhyanga, and oral medications. Vyanga is correlated with melasma in the modern aspects, it is a chronic, acquired cutaneous characterised by hypopigmented patches on sun exposed areas of the face. Ayurveda cures the root cause of any problem. Any activity that increases the fire or heat in the body increase Pitta and can lead to skin diseases.